(untitled) (Research, Society and Development, 2020)
The present study consists of evaluating the economic feasibility in installation configurations for photovoltaic systems. Scenario 1 discards the installation of a photovoltaic system in the grid to fully meet the energy consumption of the case study residence and Scenario 2 addresses the installation of a hybrid system (photovoltaic and solar thermal) to meet the total consumption of the same residence and finally, compare and choose the best option for the investor, make the economic point of view. Conduct a case study in a residence, located in the municipality of Sobrália-MG, where from the history of energy consumption will use the electricity bill of the residence and some technical and financial information and respect for the use of photovoltaic energy, was dimensioned in a photovoltaic system in the grid and a hybrid system (photovoltaic system in the grid and solar thermal) and, based on them, a financial analysis, for each scenario of meeting the energy demand of the residence, through the indicators Internal rate of return, Payback and Net Present Value over a Minimum Attractiveness Rate of 4.31% per year. The results show the economic feasibility of the proposed Scenarios 1 and 2 and, finally, found in Scenario 2, for an internal rate of return higher than in Scenario 1, in a lower return than in Scenario 1 and also a lower investment cost, it is the best option for the investor from an economic point of view.